PREVENTING THE TRAGEDY OF THE EMERGING MINERAL RESOURCE BOOM IN NORTHERN GHANA: WHAT ROLE FOR CIVIL SOCIETY ORGANISATIONS? - Anab, C.; Abazaami, J.; Achanso, S. A J. (UDS International Journal of Development, 2022)
Northern Ghana has become a hub for mining with both small- and large-scale mining actively taking place. Whilst some development experts see this as an opportunity to lift the poorest part of Ghana out of poverty, Civil Society Organisations (CSOs) and environmentalists are concerned about the negative effects of mining on community members. This study used a mixed research approach to assess the state of mining in Northern Ghana, CSOs capacity to play their watch dog role and the concerns associated with mining in Northern Ghana. The study established that the Minerals Commission has approved five large scale mining licenses, 112 small scale licenses and 162 prospecting licenses in the zone. The study further established the CSOs capacity to be weak as many of them did not have well developed programmes in the extractive sector and lacked understanding of the relevant principles, laws, tools, and indexes related to extractive industries. The key concerns included conflicts between small-scale miners and the large-scale miners, displacement of farmers from their lands and, child labour. The study concluded on the note to strengthen the capacities of CSOs in the extractive sector to enable them advocate for transparent and responsible mining practices in Northern Ghana. Keywords: Environment, Extractive Industries, Mining, Northern Ghana, Civil Society Organisations